Answer:
h= -8/3
Picture Explanation:
- Divide 3 on both sides of the equal sign, as shown above, so (h) can be alone.
- Since negative 8, let alone positive 8, can't be divided into 3, you simply leave the fraction as is. So you're left with (h= -8/3)
<em><u>Hope this makes sense.</u></em>
Answer:
GIRL NO WAY IM LITTERALY TAKING THAT TEST RN AND IM TRYING TO FIGURE OUT THAT SAME QUESTION LOL
Step-by-step explanation:
BUT I THINK ITS -0.5 DONT TAKE MY WORD FOR IT IM JUST ASSUMING ITS THE ANSWER BC ITS THE ONLY ONE THAT MAKES SENSE
Answer:
Time taken for the ball to hit the ground back = 3.08 s
Step-by-step explanation:
h(t)= -16t² + 48t + 4
when will rhe object come back to hit rhe ground?
When the ball is at the level.of the ground, h(t) = 0.
0 = -16t² + 48t + 4
-16t² + 48t + 4 = 0
Solving the quadratic equation
t = 3.08 s or t = -0.08 s
Since the time cannot be negative,
Time taken for the ball to hit the ground back = 3.08 s
Hope this Helps!!!
Step-by-step explanation:
Answer:3
x
−
2
y
=
7
Explanation:
Write the standard form of the line that goes through
(
3
,
1
)
and is perpendicular to
y
=
−
2
3
x
+
4
.
The equation
y
=
−
2
3
x
+
4
is in slope intercept form
y
=
m
x
+
b
where
m
= slope and
b
= the
y
intercept.
The slope of this line is then
m
=
−
2
3
A perpendicular slope is the opposite sign reciprocal. So, we change the sign of
−
2
3
and switch the numerator and denominator.
Perpendicular slope
m
=
3
2
To find the equation of the new line, use the point slope equation
y
−
y
1
=
m
(
x
−
x
1
)
where
m
=
slope and
(
x
1
,
y
1
)
is a point.
The slope is
3
2
and the point is the given point
(
3
,
1
)
.
y
−
1
=
3
2
(
x
−
3
)
a
a
a
Distribute
y
−
1
=
3
2
x
−
9
2
Standard form is
a
x
+
b
y
=
c
where
a
,
b
and
c
are integers and
a
is positive.
a
a
2
(
y
−
1
=
3
2
x
−
9
2
)
a
a
a
Multiply the equation by
2
a
a
a
a
a
2
y
−
2
=
3
x
−
9
−
3
x
a
a
a
a
a
a
a
−
3
x
a
a
a
Subtract
3
x
from both sides
−
3
x
+
2
y
−
2
=
−
9
a
a
a
a
a
a
a
a
+
2
a
a
a
+
2
a
a
a Add 2 to both sides −
3
x
+
2
y
=
−
7
−
1
(
−
3
x
+
2
y
=
−
7
)
a
a
a
Multiply the equation by −
1
3
x
−
2
y
=
7